Reducing inequalities in access to health care: developing a toolkit through action research. Issue 5 (29th September 2005) - Goyder, E C; Blank, L; Ellis, E; Furber, A; Peters, J; Sartain, K; Massey, C
Abstract : Problem: Healthcare organisations are expected both to monitor inequalities in access to health services and also to act to improve access and increase equity in service provision. Design: Locally developed action research projects with an explicit objective of reducing inequalities in access. Setting: Eight different health care services in the Yorkshire and Humber region, including community based palliative care, general practice asthma care, hospital based cardiology clinics, and termination of pregnancy services. Key measures for improvement: Changes in service provision, increasing attendance rates in targeted groups. Strategies for change: Local teams identified the population concerned and appropriate interventions using both published and grey literature. Where change to service provision was achieved, local data were collected to monitor the impact of service change. Effects of change: A number of evidence based changes to service provision were proposed and implemented with variable success. Service uptake increased in some of the targeted populations. Lessons learnt: Interventions to improve access must be sensitive to local settings and need both practical and managerial support to succeed. It is particularly difficult to improve access effectively if services are already struggling to meet current demand. Key elements for successful interventions included effective local leadership, identification of an intervention which is both evidence based and locally practicable, and identification of additional resources to support increased activity. A "toolkit" has been developed to support the identification and implementation of appropriate changes.